(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In-service induction isobligatory on the part of the teachers who should be familiar with the modernmethods; approaches, techniques and other recent trends involving theapplication of educational principles. Despite having vast resources andmanpower, most of our teachers do not keep intellectually alert and there islittle, inducement for them to do. It is extraordinary that our schoolteacherslearn all that is necessary for the subject that they teach, before reachingthe age of 24 or 25, much future education is left to experience, which isanother name for stagnation. The in-service education that gears up teacher’spotential has to be organized in such a way that the teachers realize therelevance of the course material to their own classroom practice. It must include lectures,workshops, group discussions, tutorial, sessions, demonstrations and microteaching. Since an ounce of demonstration is worth a pound of theory, noteacher training course will be completed without demonstration and peerteaching sessions. By and large, teacher education would provide a strong basefor quality education in the future. If the nation wants to achieve itseducational objectives of developing human resource for the promotion of socialjustice, the thrust area in the sphere of education shall be teacher’sdevelopment. It will help the government that has a larger responsibility topromote excellence at all levels of the educational pyramid.